(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The author wants to stage about the attachment relationship between young children, and their parents and about the roots of this relationship in the parents’ own attachment experiences. What is attachment? For the moment, we will speak about children as being attached, if they have a tendency to seek proximity to and contact with a specific caregiver in times of distress, illness and tiredness (Bowlby, 1984). The emergence of attachments in the first year of life will be described, as well as the determinants of individual differences in attachment. The consequences of infant attachments will be discussed in relation to longitudinal attachment studies from infancy to adulthood. Attachment is a major developmental milestone in the child’s life and it will remain an important issue throughout the life-span. The development of attachment can be described in two ways. First, a global description can be given of the phases in which attachment develops as a species-specific phenomenon. Second, attachment can be described by looking at individual differences within this species-specific development. In this article the author had tried to examine infants’ social and emotional relationships. Infants form strong bond with caregivers very early in life. They come to know, become attached to, and show a desire to be with a small very select group of people in their lives. The wonderful emotional bonds formed with infants are among the greatest rewards of parenting or care giving. These strong bonds also pose challenges. Babies who are abused or neglected, who do not have caregivers that respond to their needs, or who for other reasons have come to doubt the trustworthiness of the world will not resolve this emotional conflict in a positive way. They may be impaired from entering into relationships with others and may be wary of new situations or people. They may be unable to advance to later stages of psychosocial development, and so are more likely to suffer mental health problems later in life.